The role of empathy in choosing rewards from another's perspective - O'Connell, Garret; Christakou, Anastasia; Haffey, Anthony T.; Chakrabarti, Bhismadev (Frontiers in Human Neuroscience, 2013)
As social animals, we regularly act in the interest of others by making decisions on their behalf. These decisions can take the form of choices between smaller short-term rewards and larger long-term rewards, and can be effectively indexed by temporal discounting. In a temporal discounting paradigm, a reward loses subjective value with increasing delay presumably because it becomes more difficult to simulate how much the recipient (e.g. future self) will value it. If this is the case, then the value of delayed rewards should be discounted even more steeply when we are choosing for someone whose feelings we do not readily simulate, such as socially distant strangers. Second, the ability to simulate shows individual differences and is indexed by trait empathy. We hypothesised that individuals high in trait empathy will more readily simulate, and hence discount less steeply for distant others, compared to those who are low on trait empathy. To test these predictions, we asked 63 participants from the general population to perform a temporal discounting task from the perspectives of close and distant others, as well as their own. People were found to discount less steeply for themselves, and the steepness of temporal discounting increased with increasing distance from self. Additionally, individuals who scored high in trait empathy were found to discount less steeply for distant others compared to those who scored low. These findings confirm the role of empathy in determining how we choose rewards for others.